Cosmological constraints from unWISE and Planck CMB lensing tomography. Issue 12 (13th December 2021) - Krolewski, Alex; Ferraro, Simone; White, Martin
Abstract: A number of recent, low-redshift, lensing measurements hint at a universe in which the amplitude of lensing is lower than that predicted from the ΛCDM model fit to the data of the Planck CMB mission. Here we use the auto- and cross-correlation signal of unWISE galaxies and Planck CMB lensing maps to infer cosmological parameters at low redshift. In particular, we consider three unWISE samples (denoted as "blue", "green" and "red") at median redshifts z ∼ 0.6, 1.1 and 1.5, which fully cover the Dark Energy dominated era. Our cross-correlation measurements, with combined significance S / N  ∼ 80, are used to infer the amplitude of low-redshift fluctuations, σ8 ; the fraction of matter in the Universe, Ω m ; and the combination S8  ≡ σ8 (Ω m /0.3) 0.5 to which these low-redshift lensing measurements are most sensitive. The combination of blue, green and red samples gives a value S m  = 0.784 ± 0.015, that is fully consistent with other low-redshift lensing measurements and in 2.4σ tension with the CMB predictions from Planck. This is noteworthy, because CMB lensing probes the same physics as previous galaxy lensing measurements, but with very different systematics, thus providing an excellent complement to previous measurements.